Developing a patient individualized flexible silicone implant using SLS and vacuum die casting - Launhardt, Martin; Ebel, Nina; Kondruweit, Markus; Weyand, Michael; Volk, Tilmann; Drummer, Dietmar (AIP conference proceedings, 2019)
Heart failure is a progressive and medically complex disease, which eventually requires heart transplantation. However, an internal flexible cardiac supporting device could support the patient’s heart until a donor organ is available or might even improve cardiac function to an extent that transplantation becomes unnecessary. Technically, this requires patient individualized geometries, flexible structures and reinforcements such that compression forces only affect the heart but not the surrounding organs. The Selective Laser Sintering process (SLS) allows the manufacturing of complex thermoplastic parts without the need for an expensive mold. However, the available material portfolio is very narrow and yet does not offer a silicone rubber type material, which can be used for medical applications. Thus, in this approach the applicability of SLS vacuum die casts for the manufacturing of patient individualized flexible silicone implants shall be analyzed. Basic studies on the molding and demolding of silicone specimens using SLS vacuum die casts are investigated as well as the possibility for including flexible reinforcement structures. First, simplified mechanical tests show the feasibility of the manufacturing process as well as optimization potential using patient individualized geometries. First functional silicone heart supporting structures are successfully manufactured and can be used for medical in-vitro tests.